2015
DOI: 10.1038/srep12870
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor-15: a p53- and demethylation-upregulating gene represses cell proliferation, invasion and tumorigenesis in bladder carcinoma cells

Abstract: Growth differentiation factor-15 (GDF15),Urinary bladder carcinoma is the fourth leading malignancy in American males and the eighth most common cause of malignancy-related death 1 . Approximately 20% to 25% of primary bladder cancers have invaded the muscle layer of the bladder wall by the time they were diagnosed, and thus suggesting a poor prognosis; in addition, seventy percent of papillary and superficial tumors recur within two years of surgical excision 2 . Because the effective strategies for early det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 42 publications
(57 reference statements)
1
41
0
Order By: Relevance
“…Maspin belongs to the serine protease inhibitor/noninhibitor superfamily and has dissimilar effects according to the types of cancer [4]. Although reports concerning the biological function of maspin in bladder cancer are still contradictory, our previous studies have indicated that maspin is the downstream gene of the prostate-derived Ets factor (PDEF) and growth differentiation factor 15 (GDF15), which are antitumor genes in bladder carcinoma cells [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maspin belongs to the serine protease inhibitor/noninhibitor superfamily and has dissimilar effects according to the types of cancer [4]. Although reports concerning the biological function of maspin in bladder cancer are still contradictory, our previous studies have indicated that maspin is the downstream gene of the prostate-derived Ets factor (PDEF) and growth differentiation factor 15 (GDF15), which are antitumor genes in bladder carcinoma cells [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The expression vector with full-length human maspin cDNA was purchased from Invitrogen. Electroporation was conducted with the ECM 830 system (BTX, San Diego, CA, USA) by setting the voltage at 180 V, setting the pulse length at 90 milliseconds, and using a single pulse setting, as described in a previous method [18]. The mock-transfection cells were transfected with a control of a pcDNA3 expression vector and clonally selected in the same manner as the gene-overexpressed cells.…”
Section: Expression Vector Constructs and Stable Transfectionmentioning
confidence: 99%
“…The NDRG1 (−4714 to +46) reporter vectors were constructed as described previously51. A 5.2 kbp DNA fragment was subtracted from a BAC clone (PR11-998D10; Invitrogen) and cloned into the pGEM-3 vector (Promega BioScience) with the Kpn I cutting site.…”
Section: Methodsmentioning
confidence: 99%
“…NAG-1 expression reduces TNF-α secretion in macrophages [10], and ectopic expression of NAG-1 causes cell growth arrest [6, 8]. Furthermore, overexpression of NAG-1 in human colon, bladder, and glioblastoma cells inhibits tumor formation in the nude mouse model [4, 6, 110]. The principal function, receptor, and signaling pathway of NAG-1 remain uncertain in cancer, and the biological role of NAG-1 in diseases remains poorly understood with sometimes contradictory evidence.…”
Section: Secreted Proteins (Mmps and Nag-1)mentioning
confidence: 99%